All-digital calibration algorithm based on channel multiplexing for TI-ADCs. (August 2022) - Xie, XiMing; Chen, HongMei; Yin, YongSheng; Wang, Jian; Li, Long; Deng, HongHui; Meng, Xu
Abstracts: An adaptively calibration structure featured by channel multiplexing that can simultaneously calibrate the offset, gain, and timing mismatch errors existing in TI-ADC (Time-Interleaved ADC) channels in pure digital domain is proposed, which focuses on the problem of limited input signal bandwidth and high calibration hardware overhead. In error compensation aspect, these three mismatch errors are compensated simultaneously by adaptive method. The gain mismatch compensation employed here can help to overcome the deviation that would exist when the first-order Taylor compensation was employed alone for the timing mismatch, which can significantly improve the calibration effect in high-frequency band instead of employing complex high-order Taylor compensation structure. The total calibration algorithm is implemented using FPGA. For the 4-channel, 1 GS/s and 14-bit TI-ADC, the signal-to-noise distortion ratio (SNDR) of the system is increased from 26.19 dB to 84.37 dB, and the spurious free dynamic range (SFDR) is increased from 29.35 dB to 98.49 dB when the input signal normalized frequency f in / f s is 0.975.